Use of Extracorporeal Oxygenation (ECMO) in Intensive Care (Research, Society and Development, 2021)
Objective: To evaluate whether the use of ECMO in patients with respiratory distress in intensive care, compared to patients who did not undergo intervention, improves their prognosis. Methods: Systematic review performed on the Medical Literature Analysis and Retrieval System Online platform, accessed by the Virtual Health Library and at PUBMED, database of the U.S. National Library of Medicine. Descriptors in Health Sciences in English were used: Extracorporeal Membrane Oxygenation, Critical Care, Respiratory Distress Syndrome and Clinical Trial, totaling 77 articles. The filters used involved the availability of the full text, in which 58 articles were presented, published from the year 2011, reaching 49 articles and randomized clinical studies, totaling 10 articles, and no duplicate documents were found in the eligible databases. Results: ECMO showed significant results and with morbidity and mortality rates well below compared to conventional treatments, although, in some situations, it is limited, requiring the use of adjuvant therapies, preventive and intensive care, which together result in a greater chance of survival and guarantees an exponential increase in prognosis improvement. Conclusion: It was analyzed that ECMO therapy showed significant results and with morbidity and mortality well below conventional therapies. Although these results are positive for the use of ECMO, in some situations it is limited, requiring the use of adjuvant therapies.